Access to High School Arts Education: Why Student Participation Matters as Much as Course Availability - M. Kathleen Thomas; Priyanka Singh; Kristin Klopfenstein; Thomas C. Henry (Arizona State University, 2013)
There is renewed interest in the role of arts education in the curriculum of U.S. public schools not only because of the intrinsic value of the arts and its believed impact on achievement, but because cultivating creativity is thought to promote innovation and fuel economic growth. Still, we know little about basic access to arts education. Using individual-level administrative data from The University of Texas at Dallas Education Research Center (UTD-ERC), we develop several distinct indices of access to identify high schools rich in the arts. We find that high schools offering an extensive number of courses in the arts do not necessarily enjoy high rates of student participation. Policymakers who examine access based only on course counts in the arts will identify predominately large, non-rural high schools as having arts-rich environments. Evaluating arts programs along a single dimension, as is common in federal reports and other studies, fails to provide an accurate representation of access to arts education. Any examination of access to arts education should jointly consider course availability and student engagement in the arts. Policymakers can follow our approach and develop similar indices to assess the current state of arts education in their states.